VNS paired with training enhances recognition memory: mechanistic insights from proteomic analysis of the hippocampal synapse - Jung, Seung H.; Olsen, Laura K.; Jones, Krysten A.; Moore, Raquel J.; Harshman, Sean W.; Hatcher-Solis, Candice N. (Frontiers in Molecular Neuroscience, 2024)
IntroductionRecognition memory, an essential component of cognitive health, can suffer from biological limitations of stress, aging, or neurodegenerative disease. Vagus nerve stimulation (VNS) is a neuromodulation therapy with the potential to improve cognitive function. This study investigated the effectiveness of multiple sessions of VNS to enhance recognition memory in healthy rodents and the underlying cognitive benefits of VNS by proteomic analysis of the synaptosome.MethodsRats demonstrated VNS-induced recognition memory improvements using a novel object recognition (NOR) task. Using the LC–MS/MS method, roughly 3,000 proteins in the synaptosome of the hippocampus were analyzed.ResultsProtein–protein interaction (PPI) enrichment analysis found differentially expressed proteins related to synaptic signaling and neurotransmitter pathways. PPI network analysis identified six unique protein clusters, including a cluster of synaptic signaling related pathways. Using ingenuity pathway analysis (IPA), rapamycin-insensitive companion of mTOR was identified as an upstream regulator of synaptosome changes due to VNS-paired training.DiscussionBased on these results, it is proposed that VNS may mediate cognitive enhancement via increases in glutamatergic signaling and early LTP during the consolidation period, followed by sustained synaptic plasticity via modified post-synaptic receptor expression and dendritic outgrowth. Further investigation is required to determine if VNS is a good candidate to ameliorate cognitive impairment.